Screening of endophytic fungi as potential antagonistic agents of Pyricularia oryzae and evaluation of their ability in producing hydrolytic enzymes - NOVIA DWI PUTRI; LILIEK SULISTYOWATI; LUQMAN QURATA AINI; ANTON MUHIBUDDIN; IRISA TRIANTI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Putri ND, Sulistyowati L, Aini LQ, Muhibuddin A, Trianti I. 2022. Screening of endophytic fungi as potential antagonistic agents of Pyricularia oryzae and evaluation of their ability in producing hydrolytic enzymes. Biodiversitas 23: 1048-1057. One of the most important phytopathogenic fungi is Pyricularia oryzae, as it is the causative agent of rice blast diseases, which is the most destructive and detrimental disease in rice. Biological control using endophytic fungi can be an alternative to control blast diseases. Endophytic fungi are fungi that colonize internal plant tissues without apparently damaging the host. The aim of this study was to isolate endophytic fungi that produce hydrolytic enzymes and to investigate their ability to suppress blast disease. In this study, fifty strains of endophytic fungi were successfully obtained from rice leaves. Three fungi with the highest inhibition against P. oryzae were identified as Trichoderma asperellum, Curvularia chiangmaiensis, and Fusarium solani by analyzing fungal ITS sequence. They can produce chitinase ranging from 1.43 to 151 ?g/mL and cellulase ranging from 1.83 to 4.09 ?g/mL, which were hydrolytic enzymes that account for the lysis of phytopathogens. This enzymatic activity can cause damage and degradation of cell walls. SEM results revealed that these endophytic fungi probably excreted wall lytic enzymes or antifungal substances, inflicting wrinkles and disintegrating P. oryzae mycelium.